Relationship between age and various muscle quality indices in Japanese individuals via bioelectrical impedance analysis (BIA) - Kazushige Oshita; Akihisa Hikita; Ryota Myotsuzono; Yujiro Ishihara (Journal of Physiological Anthropology)
Abstract Background Bioelectrical impedance analysis (BIA) is widely used as a convenient method of measuring body composition. The validity of the phase angle (PhA), impedance rate (IR), and resistance rate (RR) as indices of muscle quality using BIA has been suggested. This study aimed to investigate the relationship between these muscle quality indices and age, and to clarify their characteristics. Methods The appendicular muscle mass (AMM), AMM corrected for body mass index (AMM/BMI), PhA, IR, and RR were determined using BIA in 1376 Japanese individuals (532 males and 844 females) aged 15–95 years. The PhA was determined from a 50-kHz current, and the IR and RR were determined from the impedance and resistance ratios between the 250- and 5-kHz currents. Results AMM/BMI showed greater age-related changes than the other indices of muscle mass. Significant differences in PhA, IR, and RR were found for the whole body at age ≥ 50 years and for the lower limbs at age ≥ 30 years, compared to those in their 20 s. For the arms, age-related changes were small, and significant differences in PhA of females were only observed at aged ≥ 85 years, whereas significant differences in IR and RR were observed at aged ≥ 75 years, compared to those in their 20s. Conclusion These results suggest that although PhA, IR, and RR in the whole body and lower limbs showed age-related changes, the change in PhA in the upper body was small, especially in females. However, IR and RR in the upper limbs of females reflected age-related changes more than PhA.